1997
DOI: 10.1074/jbc.272.4.2520
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of the Rat unc-13 Homologue Munc13-1 with the N Terminus of Syntaxin

Abstract: unc-13 mutants in Caenorhabditis elegans are characterized by a severe deficit in neurotransmitter release. Their phenotype is similar to that of the C. elegans unc-18 mutation, which is thought to affect synaptic vesicle docking to the active zone. This suggests a crucial role for the unc-13 gene product in the mediation or regulation of synaptic vesicle exocytosis. Munc13-1 is one of three closely related rat homologues of unc-13. Based on the high degree of similarity between unc-13 and Munc13 proteins, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
231
3
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(253 citation statements)
references
References 45 publications
13
231
3
2
Order By: Relevance
“…Mammalian homologues munc13-1, -2, and -3 (munc13s) were originally cloned from rat brain, and similar to Unc-13 they possess both DAG-and Ca 2ϩ -binding domains (Brose et al, 1995). Syntaxin, synaptobrevin, SNAP 25 (Betz et al, 1997), and Doc2 (Orita et al, 1997) were found to coimmunoprecipitate with munc13s, consistent with the suggestion that this new family of DAG-binding proteins is involved in vesicle trafficking and neurotransmitter release. Recently we cloned a human renal homologue, hmunc13, which is expressed in cultured renal mesangial and cortical epithelial cells (Song et al, 1998).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Mammalian homologues munc13-1, -2, and -3 (munc13s) were originally cloned from rat brain, and similar to Unc-13 they possess both DAG-and Ca 2ϩ -binding domains (Brose et al, 1995). Syntaxin, synaptobrevin, SNAP 25 (Betz et al, 1997), and Doc2 (Orita et al, 1997) were found to coimmunoprecipitate with munc13s, consistent with the suggestion that this new family of DAG-binding proteins is involved in vesicle trafficking and neurotransmitter release. Recently we cloned a human renal homologue, hmunc13, which is expressed in cultured renal mesangial and cortical epithelial cells (Song et al, 1998).…”
Section: Introductionmentioning
confidence: 62%
“…A number of SNARE proteins, such as yeast Sed5p (Banfield et al, 1994) and mVps45 (Tellam et al, 1997), mammalian syntaxin 6 (Bock et al, 1997), VAMP4, Syntaxin 13, and mVtib (Advani et al, 1998), have all been reported to be localized to the Golgi. Rat munc13-1 has been shown to interact with a number of proteins involved in vesicle docking and trafficking, such as syntaxin (Betz et al, 1997) and Doc2 (Orita et al, 1997). Interaction of munc13-1 and Doc2 was stimulated by DAG and has been suggested to be involved in Ca 2ϩ -dependent exocytosis (Orita et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast Two-hybrid Assays-The yeast two-hybrid screen was performed as described (15) in L40 cells using pLexN with the N-terminal domain of mouse vti1b (amino acids 1-128) as bait vector and a library derived from rat E18 embryonic brain RNA in pVP16 -3 as prey vector (16). Positive cells were selected on plates with minimal medium lacking uracil, lysine, tryptophan, leucine, and histidine complemented with 2.5 mM 3-aminotriazole.…”
Section: Methodsmentioning
confidence: 99%
“…131 Munc13s unfold and activate the SNARE protein syntaxin and promote the formation of the SNARE complex. [131][132][133] In addition, recent studies have shown that Munc13 proteins play an important role in potentiation of neurotransmitter release in short-term synaptic plasticity. 125 Rosenmund et al 125 using knockout mice for Munc13-1 and Munc13-2, have shown that in cultured hippocampal neurons there are two functional classes of synapses depending on the differential localization of Munc13-1 and Munc13-2 in the same neuron along a single axon.…”
Section: Munc13 Proteinsmentioning
confidence: 99%